Inflammation and vascular responses to acute mental stress: implications for the triggering of myocardial infarction - Paine, Nicola J.; Bosch, Jos A.; Veldhuijzen van Zanten, Jet J. C. S. (Current pharmaceutical design, 2012)
There is evidence that mental stress can trigger myocardial infarction. Even though the underlying mechanisms remain to be determined, both inflammation an...
Gesehen am 22.05.2018